Challenges to Seagrass Restoration in the Indian River Lagoon, Florida - Vivienne A. Main; Morgan K. Gilligan; Sarah M. Cole; Todd Z. Osborne; Ashley R. Smyth; Loraé T. Simpson (Journal of Marine Science and Engineering, 2024)
Seagrasses provide valuable ecosystem services, including improved water quality, carbon sequestration, and sediment stabilization. Unfortunately, these critical habitats are declining globally due to a range of anthropogenic impacts. Restoration practitioners have made efforts to mitigate loss through the introduction of seagrass transplants. However, seagrass restoration has low success rates and is plagued by water quality concerns and ecosystem degradation. Studies to improve seagrass restoration efforts have targeted different functional taxa to allow for greater stability and recovery of threatened ecosystems, and excluded macro-grazers to limit losses to newly established and restored seagrasses. We hypothesized greater seagrass (Halodule wrightii) health when restored in conjunction with hard clams (Mercenaria mercenaria) and protected from grazers using herbivore exclusion devices (HEDs) in the Indian River Lagoon (IRL), Florida. While our study experienced high rates of seagrass mortality, we were able to observe significant differences in seagrass health between IRL sub-lagoons and observed the positive effects of HEDs on seagrass health. The observed high species mortality highlights how restoration in the IRL is hindered by biotic and abiotic stressors, site selection, and a lack of clear restoration protocols. As we see ongoing declines in water quality and loss of foundational species, informed site selection, greater understanding of grazer presence, and multi-species restoration will provide an informed approach for future seagrass restoration projects globally.